USE OF POLYSACCHARIDE EXTRACTED FROM TREMELLA FUCIFORMIS BERK FOR CONTROL DIABETES INDUCED IN RATS. - Bach, Erna Elisabeth; Costa, Silvia Goes; Oliveira, Helenita Antonia; Junior, Jorge Silva; Silva, Keisy Menezes da; Marco, Rogerio Milton de; Hi, Edgar Matias Bach; Wadt, Nilsa Sumie Yamashita (Emirates Journal of Food and Agriculture, 2015)
Exopolysaccharides (EPS) was extracted from Tremella fuciformis growth in solid medium contained sorghum seeds. The objective of present work was analyzed EPS and evaluate the effect on the glucose, cholesterol, HDL, triglycerides, glutamic-pyruvic transaminase (GPT), urea level in the plasma of rats with type 1 diabetes mellitus (DM1) induced by high sugar diet and streptozotocin. Beta-glucan and total sugar from T. fuciformis was determined and the major quantity was alfa linked glucose. Concentration used for animals was 1mmol and 2mmol of EPS. Male Wistar rats were separated in two groups where one was induced diabetes mellitus (DM1) with streptozotocin and another with high sugar diet. The rats were allocated as follows: control that received commercial pellet; control that received polysaccharide; diabetic group that received streptozotocin or high sugar diet; diabetic group that received 1mmol or 2mmol from polysaccharide obtained from different T. fuciformis isolate. In group that received streptozotocin were evaluated results until 35days but in another group with high sugar diet the results go to 60days. Weight and blood glucose levels were measured once a week and after the period from experiment the animals were euthanized and blood was collected for the analysis of cholesterol, HDL, triglycerides, GPT and urea. Results indicate that EPS is beneficial in control of DM1 when the level from blood glucose is until 130mg/dL accomplished by reducing cholesterol, triglyceride, GPT, urea and increasing HDL cholesterol. When the blood glucose level is above 200mg/dL the action of EPS in reducing is not satisfactory. The T. fuciformis solution did not show anti-inflammatory activity.